Ultrasound guided tattooing of axillary lymph nodes in breast cancer patients prior to neoadjuvant therapy, and identification of tattooed nodes at the time of surgery. Issue 6 (June 2020) - Allweis, Tanir M.; Menes, Tehillah; Rotbart, Noa; Rapson, Yael; Cernik, Hana; Bokov, Inna; Diment, Judith; Magen, Ada; Golan, Orit; Levi-Bendet, Noa; Givon Madhala, Osnat; Grubstein, Ahuva
Abstract: Background: Breast cancer patients with lymph node (LN) metastases at diagnosis often undergo neoadjuvant therapy (NAT). Identification of a LN which regressed after NAT remains a challenge. Objective: To evaluate marking of involved nodes by tattooing with carbon suspension, and identifying these nodes during surgery. Methods: A small amount (0.2–0.5 ml) of carbon suspension was injected into one or two axillary LNs under ultrasound guidance at the time of LN biopsy or before or shortly after starting NAT for LN positive breast cancer. During surgery an attempt was made to identify and remove the tattooed LN as a separate specimen. All patients underwent sentinel LN mapping and biopsy and/or axillary LN dissection as mandated by their clinical status. Results: Sixty three patients underwent tattooing of axillary LNs with no complications or adverse events. At surgery a tattooed node was identified in 60 patients (95%; 95% CI 87, 98). Of 56 patients who underwent sentinel mapping with Tc99, in 51 (91%; 95% CI 81, 96) at least one radioactive LN was identified. Of 50 patients in whom both radioactivity and tattoo were identified in axillary LNs, in 40 (80%; 95% CI 67, 89) LNs were radioactive and tattooed, however in 10 patients (20%; 95% CI 11, 33), the tattooed LN was not radioactive. Conclusions: Tattooing of axillary LNs is safe and easily performed. Tattooing was helpful in identifying the marked LN in the majority of cases. This technique helps to ensure that metastatic LNs are identified and removed at surgery after NAT.